Verantwortungsbewusste Konfliktlösungen bei embryopathischem Befund - Schumann, Eva (Universitätsverlag Göttingen, 2008)
Although the discussion of the ethical, legal and medical problems of (late) abortion, prenatal diagnosis and embryopathic findings continues since the reform of the Pregnant Women and Family Welfare Amendment Act of 1995 and the related elimination of embryopathic indication for almost fifteen years, convincing solutions are still missing. This volume contains the contributions of the 3rd Workshop on Medical Law conducted on February 26 2008. They remind of the urgent need for reform and offer suggestions for the legal policy debate. In the focus of the contributions stand the (criminal) legal and medico-ethical "evaluation" of human life before birth and the question of how the involved professionals can handle their responsibility with the issue of a embryopathic findings, to ensure that the pregnant patient receives help and support during her emotionally stressful decision-making process, but also consider the right to life of the unborn child (especially in cases of extra-uterine viable).